Factors affecting somatic cell counts and their relations with milk and milk constituent yield in buffaloes - Cerón-Muñoz, M. [UNESP]; Tonhati, Humberto [UNESP]; Duarte, J. [UNESP]; Oliveira, J. [UNESP]; Muñoz-Berrocal, M. [UNESP]; Jurado-Gámez, H. [UNESP] (American Dairy Science Association, 2002)
Data concerning daily milk yield (MY), percentage of milk fat (%F), protein (%P), lactose (%LT), and total solids (%TS), and somatic cell counts (SCC) for a herd of 222 Murrah buffalo reared in the state of São Paulo, Brazil, were collected monthly from 1997 to 2000 in order to study the factors affecting SCC and their relation to milk production and constituents during lactation. SCC decreased in the second month of lactation and increased thereafter, up to the ninth month of lactation. The interaction of month of lactation x order of calving was significant. Mean MY observed during the first month of lactation was 6.87 kg, which increased to 7.65 kg during the second month, and then decreased until the ninth month of lactation (3.83 kg). During the different months of lactation, %F, %P, %LT, and %TS ranged from 6.28 to 8.38%, 4.05 to 4.59%, 4.96 to 5.34%, and 16.94 to 18.55%, respectively. Calving year, calving order, and order of month of lactation significantly affected MY, %F, %P, %LT, and %TS. The regression coefficients of transformed SCC on MY and %LT were negative and significant during all months of lactation, showing that milk and lactose yield decreased with increased transformed SCC, causing losses to buffalo milk producers.
Keywords: Fat; Lactose; Mastitis; Milk; Protein; Total solids; Bubalus; fat; lactose; milk protein; animal; animal disease; Brazil; buffalo; cell count; chemistry; cytology; female; lactation; milk; physiology; season; secretion; time; Animals; Buffaloes; Cell Count; Fats; Female; Lactation; Milk Proteins; Seasons; Time Factors